Free-Flap Reconstruction of the Tongue - Vincent, Aurora; Kohlert, Scott; Lee, Thomas S.; Inman, Jared; Ducic, Yadranko (Seminars in Plastic Surgery, 2019)
The tongue is paramount to natural speech and swallowing, and good tongue function is important in the overall quality of life. Autologous free-flap reconstruction of the tongue after glossectomy allows for adequate speech, swallow, and quality-of-life outcomes in a majority of patients. Herein, the authors review autologous free-flap reconstruction of the tongue with a focus on different flap options, speech and swallow outcomes, quality-of-life outcomes, and factors that affect how patients perform after tongue reconstruction.
Keywords: tongue reconstruction; free tissue transfer; head and neck cancer